Strategies of Refusal Speech Act by Javanese Culture-based Students at Darul Ihsan Muhammadiyah Islamic Boarding School Sragen - Harun Joko Prayitno; Abdul Ngalim; Muhammad Rohmadi; Udik Riyanto (Journal of Education and Learning (EduLearn), 2018)
The research aims at (a) describing the strategies and identifying the levels of refusal speech act in politeness, and (b) formulating the internalization of polite values in a process of the Javanese culture-based students’ character building. The research was conducted at Darul Ihsan Muhammadiyah Islamic Boarding School Sragen. It employed a descriptive and qualitative, and analytic, critic, and holistic approach. The data sources covered all the students (santri) and teachers (asatidz) in both formal and nonformal situations. The object was the refusal speech act, spoken in the communication at the school. The data were collected with the techniques of content analysis, in-depth interview, and observation. The data were analyzed with a contextual-extralingual method. In conclusion, the results of the research show that: (a) the refusal speech act is performed through indirect (63%) and direct strategies (37%), (b) the refusal speech act is spoken through indirect communication with polite (29%), impolite (56%), cost-benefit (3%), authority (5%), and optionality (5%), and social distance (2%), (c) the internalization of the students’ character building is realized in the forms of model, habit, supervision, advice and suggestion, warning, and sanction. The dominant factors in the internalization process are closely related to the teachers’ roles, Islamic Boarding School’s environment, and politeness building in the learning process. The problems are closely related to the low understanding of politeness, heterogeneous students, and students’ habits.